Preparation, Characterization, and Biological Activity of La(III), Nd(III), Er(III), Gd(III), and Dy(III) Complexes with Schiff Base Resulted from Reaction of 4-Antipyrinecarboxaldehyde and 2-Aminobenzothiazole - Kawther Adeeb Hussein; Naser Shaalan; Aliaa Khauon Lafta; Janan Majeed Al Akeedi (Universitas Gadjah Mada, 2024)
The research includes the preparation of several complexes of the internal transition elements lanthanide (Ln = La, Nd, Er, Gd, and Dy) containing the 4f shell, with Schiff bases resulting from condensation reactions between 4-antipyrinecarboxaldehyde and 2-aminobenzothiazoles. Schiff's base was identified using FTIR spectra, UV-vis spectroscopy, elemental microanalysis CHNSO, nuclear magnetic resonance, mass spectrometry, and TGA thermal analysis. The complexes were studied and identified with elemental microanalysis CHNSO, FTIR spectroscopy, UV-vis spectroscopy, TGA thermal analysis, conductivity measurement, and magnetic sensitivity. The result showed that these complexes were classified as homogeneous bidentate complexes with the general formula of [Ln2(L)2(NO3)6]·6H2O. The physical measurements indicated that the prepared complexes are non-electrolyte and paramagnetic. Some compounds prepared in vitro were evaluated for their antibacterial activity against four types of pathogenic strains Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Klebsiella pneumonia, and using the agar disc spreading method for the evaluation. The results showed that some of these complexes have good antibacterial activity compared to the biological activity of the ligand. Also, the biological activity of Schiff's base and the prepared complexes were evaluated against three types of fungi (Candida albicans, Tropical fungi, and Scandal fungi), and they showed great activity against the prepared complexes.